Pergeseran Makna Tradisi Megengan di Masyarakat Jawa di Era Modern (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The Megengan tradition is a Javanese ritual performed before the month of Ramadan as a form of spiritual preparation, strengthening social solidarity, and maintaining relationships with ancestors. However, the development of modernization, urbanization, educational advancement, and changes in mindset have caused this tradition to experience a significant shift in meaning. This study aims to describe the changes in function, meaning, and position of Megengan in modern society using Max Weber's modernization theory as an analytical framework. The research method used is a literature study from various journals, cultural documents, and previous research related to the Megengan tradition in various regions of Java. The results show that Megengan has undergone a transformation from a sacred ritual full of cosmological symbols to a more functional and efficient socio-cultural activity. The process of rationalization in modern society has caused the spiritual and symbolic meaning of ritual foods such as apem, ketan, and ingkung to be reduced, while the form of ritual implementation has become more formal and centered on religious institutions. The change in ritual authority from elders to modern religious figures is one indication of the shift from traditional authority to rational-formal authority as explained by Weber. Despite the simplification of its meaning, Megengan remains a living tradition that serves to strengthen cultural identity, social harmony, and intergenerational relationships. This research confirms that the shift in Megengan does not indicate a weakening of Javanese tradition, but rather a form of cultural adaptation in response to the dynamics of modernity.